(untitled) (Journal of Economic Research & Business Administration, 2023)
A circular economy is an economic system in which resources are used, reused, and regenerated in a closed loop, rather than the traditional linear model of extraction, use, and disposal. The topic is particularly urgent for emerging countries as it can help address many of the economic, environmental, and social challenges these countries face. This article aims to analyze the current state of circular economy development in Kazakhstan and its progress in implementing circularity principles over the years. The research was conducted in two stages: (1) a statistical analysis based on secondary data, which identifies patterns and trends in waste recycling; (2) a regression model for evaluating the impact of management costs on the level of recycling and reuse of waste in Kazakhstan. The data was collected for the period from 2015 to 2021. The results show that solid waste recycling has increased more than 11 times, while the municipal waste generation rate per capita slightly decreased. The regression analysis demonstrates that increasing management costs does not have the desired effect on the reuse and recycling of waste, backing the previous research results about the importance of other factors like environmental consciousness and state regulation. Despite the general positive changes, the progress of Kazakhstan in implementing a circular economy is still in its early stages. The article can provide valuable insights to policymakers and researchers in Kazakhstan on ways of assessing the waste management system and promoting a circular economy in the country. Keywords: circular economy, waste management, regression analysis, environmental consciousness